Effects of olanzapine and haloperidol on mTORC1 signaling, dendritic outgrowth, and synaptic proteins in rat primary hippocampal neurons under toxic conditions. (1st November 2018) - Park, Sung Woo; Seo, Mi Kyoung; McIntyre, Roger S.; Mansur, Rodrigo B.; Lee, Yena; Lee, Jae-Hon; Park, Seon-Cheol; Huh, Lyang; Lee, Jung Goo
Highlights: B27 deprivation in hippocampal cultures decreases mTOR signaling activity. Olanzapine can actives the mTOR signaling pathway. Olanzapine increases synaptic plasticity through mTOR signaling. However, haloperidol has no such effects. Abstract: Recent studies have demonstrated that antipsychotic drugs may activate mammalian target of rapamycin complex 1 (mTORC1) signaling in neurons. However, the relationship between mTORC1 signaling activation and currently prescribed antipsychotic drugs remains incompletely understood. The purpose of this study was to determine whether alterations in the level of mTORC1 signaling occur after rat primary hippocampal neurons are treated with olanzapine and haloperidol under toxic conditions. Additionally, we investigated whether these drugs affect dendritic outgrowth and synaptic protein expression through the mTORC1 signaling pathway. We measured changes in mTORC1-mediated and synaptic proteins by Western blotting assay under toxic conditions induced by B27 deprivation. Dendritic outgrowth was determined by a neurite assay. Olanzapine significantly increased the phosphorylated levels of mTORC1, its downstream effectors, and its upstream activators. The increased mTORC1 phosphorylation induced by olanzapine was significantly blocked by specific PI3K, MEK, or mTORC1 inhibitors. Olanzapine also increased dendritic outgrowth and synaptic proteins levels; all of these effects were blocked by rapamycin. However, haloperidol had none of these effects. We demonstrated that olanzapine, but not haloperidol, activated the mTORC1 signaling pathway and increased dendritic outgrowth and synaptic proteins by activating mTORC1 signaling in rat primary hippocampal neurons. These findings suggest that olanzapine affects neuroplasticity by activating mTORC1 signaling.